The role of tamoxifen in chemoprevention of inherited breast cancer in BRCA1 mutation carriers - Jakubowska, Anna; Gronwald, Jacek; Lubiński, Jan; Menkiszak, Janusz; Oszurek, Oleg; Byrski, Tomasz; Huzarski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2002)
The carrier state of BRCA1 and/or BRCA2 mutation is a major risk factor in the development of breast and/or ovarian cancer. Studies on BRCA1 and BRCA2 carriers showed that carrier state of these mutations corresponds to ~80-85% risk of breast and/or ovarian cancer development. Clinical observations showing that breast cancer patients treated with tamoxifen less frequently develop the second primary tumor in a second breast than non tamoxifen users, strongly suggested that antiestrogenic agents may be also useful in prevention of breast cancer in healthy women. Clinical trials conducted later proved beneficial influence of antiestrogen agents including tamoxifen on the reduction of breast cancer incidence in population of healthy women [The National Surgical Adjuvant Breast and Bowel Project P1 Study (NSABP-P1) ]. In this trial the risk reduction was estimated at the level of 50%. A later clinical study concerned antiestrogen agents effect on breast cancer risk reduction in subgroups of patients with an extremely high risk of this neoplasm including BRCA1 mutation carriers. The results of the major trials on tamoxifen use in the prevention of breast cancer including hereditary cases in BRCA1 mutation carriers are presented and critically discussed in this paper. The data of the multicenter trial conducted by Narod and al. obtained in the largest group - 539 BRCA1 mutation carriers - proved positive effect of tamoxifen on breast cancer risk reduction.